Raw spectra data alongside derived concentrations from the Cataract Scout Park, Australia, taken during the COALA-2020 campaign - Possell, Malcolm; Parnell, Danica; Guenther, Alex; Ramirez-Gamboa, Jhonathan; McDougall, Hamish; Paton-Walsh, Clare; Simmons, Jack B (PANGAEA, 2022)
Raw spectra data in .cdf format alongside derived concentrations from the Cataract Scout Park, Australia, taken during the COALA-2020 campaign.
Keywords: Australia; Biogenic VOC; Emissions; thermal desorption